The Judicial Assessment of ‘Expert Evidence’ in the United Kingdom’s Immigration and Asylum Chamber - John R. Campbell (Laws, 2022)
This paper examines the role of cultural evidence submitted by anthropologists and social scientists to assist individuals seeking asylum in the United Kingdom. Expert evidence is an essential element in the way that Immigration Judges decide asylum claims. The paper begins by looking at the role of experts and the limits of scientific evidence in the legal process. I set out the context in which expert evidence features in the First-Tier Tribunal of United Kingdom’s Immigration and Asylum Chamber (IAC). I then show how Immigration Judges in the Upper Tribunal of the IAC assess expert evidence in ‘country guidance’ cases decided between 2015 and 2019. Analysis reveals that experts submit a range of different types of evidence, that judges problematically assess this evidence and that there are serious defects in the judicial process. I conclude by suggesting ways to mediate between the very different roles, perceptions and training of experts, lawyers and judges.